Bispecific antibodies - Kontermann, Roland 1961- (Springer ebooks., 2011)
The concept of using bispecific antibodies for cancer therapy by retargeting immune effector cells was developed more than 25 years ago. However, initial clinical studies were rather disappointing mainly due to low efficacy, severe side effects and the immunogenicity of the bispecific antibodies. A deeper understanding of effector cell biology and especially developments in the field of antibody engineering has led to the generation of new classes of bispecific antibodies capable of circumventing many of these obstacles. Furthermore, new applications were established for bispecific antibodies, such as pre-targeting strategies in radioimmunotherapy and dual targeting approaches in order to improve binding, selectivity and efficacy. In this book, the different means of generating bispecific antibodies are described, with an emphasis on recombinant formats, and information on the various applications of bispecific antibodies, e.g. in cellular cancer immunotherapy, radioimmunotherapy and pre-targeting strategies, but also on emerging applications such as dual targeting strategies, i.e., the simultaneous inhibition of two targets (cytokines, receptors, etc.) are provided. This book is intended for a broad readership in the field of antibody engineering, mainly from the pharmaceutical and biotechnology sector, but also including academic researchers working with the subject